Opuść nawiasy i zredukuj wyrazy podobne
dla wyjaśnienia np. 1/8 to jedna ósma
a) (6a ² - a - 2) - (2a ² - a) + (4a - 2) + (a ² -1) =
b) (m - 3n + 1) + (2m + n - 1) - (3m - 2n + 2) =
c) (6,2a - 2,5ab + 3b) - (4,8 + 3b - 2,5ab) =
d) ( 1/5x - 4y + 1/2) + (4/5x + 2y - 1/4 ) - (3/4 + y) =

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T22:17:08+01:00
A) (6a ² - a - 2) - (2a ² - a) + (4a - 2) + (a ² -1) =
6a²-a-2-2a²+a+4a-2+a²-1=5a²+4a-5


b) (m - 3n + 1) + (2m + n - 1) - (3m - 2n + 2) =
m-3n+1+2m+n-1-3m+2n-2=-2

c) (6,2a - 2,5ab + 3b) - (4,8 + 3b - 2,5ab) =
6,2a-2,5ab+3b-4,8-3b+2,5ab= 6,2a-4,8

d) ( 1/5x - 4y + 1/2) + (4/5x + 2y - 1/4 ) - (3/4 + y) =
⅕x-4y+½+⅘x+2y-¼-¾-y= x-3y-½
2010-03-25T22:21:47+01:00
A) (6a kwadrat -a-2)-(2a kwadrat-a)+(4a-2)+(a kwadrat-1)=
6a kwadrat-a-2-2a kwadrat+a+4a-2+a kwadrat-1=5a kwadrat+4a-5

b) (m-3n+1)+(2m+n-1)-(3m-2n+2)=
m-3n+1+2m+n-1-3m+2n-2=-2

c) (6,2a-2,5ab+3b)-(4,8+3b-2,5ab)=
6,2a-2,5ab+3b-4,8-3b+2,5ab=6,2a-4,8

d) (1\5x-4y+1\2)+(4\5x+2y-1\4)-(3\4+y)=
1\5x-4y+1\2+4\5x+2y-1\4-3\4-y=x-3y-2\4